Unveiling non-linear water effects in near infrared spectroscopy: A study on organic wastes during drying using chemometrics. (1st March 2021) - Mallet, Alexandre; Charnier, Cyrille; Latrille, Éric; Bendoula, Ryad; Steyer, Jean-Philippe; Roger, Jean-Michel
Graphical abstract: Summary of methodology: near infrared spectral variations related to moisture content variations are obtained for a variety of substrates, and application of principal components analysis is used to analyze the effects of water. The biochemical characteristics of substrates are obtained to investigate water effects' dependency to chemical types. Highlights: A comprehensive experimentation to study water effects on spectra. Principal components analysis is used to decompose these effects. Water effects on spectra are complex: they mix both physical and chemical effects. These vary upon the nature of wastes and the moisture content range considered. Abstract: In the context of organic waste management, near infrared spectroscopy (NIRS) is being used to offer a fast, non-destructive, and cost-effective characterization system. However, cumbersome freeze-drying steps of the samples are required to avoid water's interference on near infrared spectra. In order to better understand these effects, spectral variations induced by dry matter content variations were obtained for a wide variety of organic substrates. This was made possible by the development of a customized near infrared acquisition system with dynamic highly-resolved simultaneous scanning of near infrared spectra and estimation of dry matter content during a drying process at ambient temperature. Using principal components analysis, the complex water effects on near infrared spectra are detailed. Water effects are shown to be a combination of both physical and chemical effects, and depend on both the characteristics of the samples (biochemical type and physical structure) and the moisture content level. This results in a non-linear relationship between the measured signal and the analytical characteristic of interest. A typology of substrates with respect to these water effects is provided and could further be efficiently used as a basis for the development of local quantitative calibration models and correction methods accounting for these water effects.